the Influence of Marketing Communication on Customer Loyalty at PT. Image Express Delivery Van (TIKI) Sumedang Branch : pemasaran - ginanjar, yayat; Dewi, Kisthi Hanila; Sutisna, Nana (Ann Publisher, 2024)
Abstract. Marketing communications can be an effective form of communication channel to handle consumer complaints effectively and efficiently. By paying attention to the importance of marketing communications, companies can design more effective communication strategies to achieve their marketing goals, and can build strong customer loyalty. In this research, the method used is a quantitative method. According to Priyono (Sahir, 2021:13)